ITO nanoparticles break optical transparency/high-areal capacitance trade-off for advanced aqueous supercapacitors. Issue 48 (29th November 2017) - Bellani, Sebastiano; Najafi, Leyla; Tullii, Gabriele; Ansaldo, Alberto; Oropesa-Nuñez, Reinier; Prato, Mirko; Colombo, Massimo; Antognazza, Maria Rosa; Bonaccorso, Francesco
Abstract : Indium tin oxide nanoparticles break optical transparency/high-areal capacitance trade-off for advanced aqueous supercapacitors. Abstract : The ever-increasing demand for energy storage in portable electronic devices is driving research on supercapacitor technology. In this context, optical transparency and mechanical robustness of supercapacitors are the key properties for the development of next-generation multifunctional devices, such as head-up displays, high-aesthetic touch screens and monolithic energy conversion/storage integrated systems. Here, we demonstrate that indium tin oxide nanoparticles (ITO NPs) are ideal materials for a facile solution-processed fabrication of transparent/semi-transparent electrodes with high areal capacitance ( C areal ) in aqueous solutions (1 M Na2 SO4 ), overcoming the crucial trade-off between optical transparency and areal supercapacitor performance. In particular, our ITO NP electrodes exhibit C areal values of 0.40, 0.72 1.53, 3.41, and 6.45 mF cm −2 at 0.2 mA cm −2 for a transmittance ( T ) of 81.9%, 69.7%, 64.4%, 46.6% and 26.7% at 550 nm, respectively. The C areal values at current densities higher than 1.2 mA cm −2 are record-high ( i.e., 0.81, 1.76 and 3.17 mF cm −2 at 10 mA cm −2 for a T of 64.4%, 46.6% and 26.7% at 550 nm). Indium tin oxide nanoparticle electrodes show 94% capacitance retention over 10 000 charge–discharge cycles. Flexible electrodes are also designed on a polyethylene terephthalate substrate, showing operational activity over 100 bending cycles under curvature radii of 1 and 0.5 cm. Finally, the coating of the ITO NP electrode with a photoactive polymer, i.e., rr-poly(3-hexylthiophene), permits the fabrication of a light-powered supercapacitor, as a clear-cut case of an innovative hybrid electric power delivery device, storing an energy density of 17.54 nW h cm −2 under simulated sunlight illumination.